Flame retardant concentrations and profiles in wild birds associated with landfill: A critical review - Tongue, Andrew D.W.; Reynolds, S. James; Fernie, Kim J.; Harrad, Stuart (Environmental pollution (1987), 2019)
Given factors such as their persistence and toxicity, legacy brominated flame retardants (BFRs) like polybrominated diphenyl ethers (PBDEs) and hexabromocyclododecane (HBCDD), are designated as persistent organic pollutants (POPs) and are subject to regulation. Waste streams likely represent a substantial reservoir of legacy BFRs given that they were once widely applied to goods which are increasingly likely to be obsolete. Waste streams are also increasingly likely to be a source of emerging flame retardants, in particular, novel BFRs (NBFRs), the halogenated norbornene flame retardant Dechlorane Plus (DDC-CO) and the brominated, chlorinated or non-halogenated organophosphate triester flame retardants (PFRs). Many bird populations rely on landfill and its surrounding land-use for inter alia the opportunities it provides for activities such as foraging and resting. However, studies on captive and wild (free-living) birds have demonstrated deleterious effects of several FRs. Globally, approximately 250 bird species, including many of conservation concern, are reported to use landfill and surrounding habitat (including wastewater treatment operations), thus putting birds potentially at risk of exposure to such chemicals. We synthesise and critically evaluate a total of 18 studies covering eight avian species published between 2008 and 2018 (inclusive) across four continents that report flame retardant (FR) burdens in birds utilising landfill. Several such studies found FRs at among the highest concentrations detected in wild biota to date. We recommend that ongoing research be focused on landfill-associated birds, given that landfill is an important source of FRs and other anthropogenic chemicals, and particularly at sites where species are of conservation concern. We suggest ways in which the comparative power of studies could be enhanced in the future, the reporting of a minimum common suite of key chemicals, and where feasible, standardisation of the tissue compartments (i.e., eggs) to be studied. We conclude by identifying future research directions. [Display omitted] •Landfill provides a predictable anthropogenic food source for many bird species.•Landfill has been shown to be a reservoir of brominated flame retardants (BFRs).•BFRs are known to exert a range of deleterious effects on birds.•We reviewed studies documenting BFRs and other FRs in landfill-associated birds.•Such birds exhibit elevated flame retardant levels compared to reference birds.